Mutations in the CEP290 (NPHP6) Gene Are a Frequent Cause of Leber Congenital Amaurosis - den Hollander, Anneke I. (The American Society of Human Genetics, 2006)
Leber congenital amaurosis (LCA) is one of the main causes of childhood blindness. To date, mutations in eight genes have been described, which together account for ∼45% of LCA cases. We localized the genetic defect in a consanguineous LCA-affected family from Quebec and identified a splice defect in a gene encoding a centrosomal protein (CEP290). The defect is caused by an intronic mutation (c.2991+1655A→G) that creates a strong splice-donor site and inserts a cryptic exon in the CEP290 messenger RNA. This mutation was detected in 16 (21%) of 76 unrelated patients with LCA, either homozygously or in combination with a second deleterious mutation on the other allele. CEP290 mutations therefore represent one of the most frequent causes of LCA identified so far.